Pengaruh Pemberian Permen Jahe Terhadap Hyperemesis Gravidarum Pada Ibu Hamil Di Bidan Misniarti Tahun 2022 - Lasria Yolivia Aruan; Yasrida Nadeak; Ika Damayanti Sipayung (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Introduction: Non-adherence to the Therapeutic Ginger candy is a type of confectionery made from sugar and ginger. Ginger can inhibit the inflammatory process caused by H. pylori infection. therefore, the frequency of hyperemesis gravidarum caused by H. pylori infection can be reduced. Hyperemesis gravidarum is a complaint of severe nausea and vomiting more than 10 times a day during pregnancy which can cause fluid deficiency, weight loss, or electrolyte disturbances, thus interfering with daily activities and endangering the fetus in the womb. Objectives: aims to determine the effect of giving ginger candy to hyperemesis gravidarum in pregnant women at Misniarti Midwife Practice Method: This study is a Quasi-Experimental study with the One Group Pretest Posttest design. In this design before the treatment is given, the sample The results of the study stated that out of 10 respondents there were 7 respondents (70%) giving ginger candy frequently and mild hypermesis gravidarum, there were 2 respondents (20%) giving ginger candy rarely and moderate hypermesis gravidarum, while 1 respondent (10%) giving ginger candy not ever and severe hypermesis gravidarum. The results of the analysis show that the probability value is (0.002) < sig_a = 0.05. The results of this analysis meet the criteria for the hypothesis of the relationship, so it can be concluded that there is an effect of giving ginger candy to hypermesis gravidarum in pregnant women at the Misniarti midwife practice. Suggestions for future researchers are expected to examine more sources and references related to this research.